Presence of δ-(l-α-Aminoadipyl)-l-Cysteinyl-d-Valine in Fermentations of Penicillium chrysogenum - Adriaens, P. (1975)
Cultures of Penicillium chrysogenum, growth with [(35)S]sulfate or labeled amino acids, were examined by ion-exchange chromatography for possible peptidic precursors of penicillin. A sulfur-containing compound, present in both the mycelial extracts and the culture filtrates, was eluted at the location of the synthetic lld-tripeptide δ-(l-α-aminoadipyl)-l-cysteinyl-d-valine. Since this compound was also labeled when the cultures were incubated with dl-[6-(14)C]α-aminoadipic acid, l-[3,3′-(3)H]cystine, or dl-[1-(14)C]valine, its identity with the synthetic lld-tripeptide can be accepted. No δ-(l-α-aminoadipyl)-l-cysteine or lll-tripeptide were detected. The implications of these findings for tripeptide and penicillin biosynthesis are discussed.